STUDENTS’ PERCEPTIONS OF GAME-BASED LEARNING IN MATHEMATICS AT THE PRIMARY LEVEL - Rachmawati, Sofi Dian; Diyah Nur Arafah, Diyah Nur Arafah; Ahimsa Putri Justitia, Ahimsa Putri Justitia; Muhammad Syahrul, Muhammad Syahrul; Atmojo, Setyo Eko (Dialektika Jurnal Pendidikan, 2026)
This study investigates primary school students' perceptions of game-based learning (GBL) in mathematics, focusing on fractions and basic geometry taught through interactive digital games including Kahoot!, Prodigy Math, and a locally adapted platform, Math Adventure. Employing a quantitative survey design, data were collected from 30 Grade 4 students (aged 9–11 years) at SD Negeri Sonosewu, Bantul, Central Java, Indonesia, using a validated 25-item Likert-scale questionnaire (five dimensions: enjoyment and engagement, perceived usefulness, ease of use, motivation to learn, and mathematical understanding; Cronbach α = .912). Descriptive statistics showed an overall mean perception score of 4.37 (SD = 0.51) out of 5, classified as very positive. All five dimensions exceeded a mean of 4.20, with motivation to learn recording the highest score (M = 4.53, SD = 0.44). Independent-samples t-tests revealed no statistically significant gender differences across all dimensions (p > .05), indicating that GBL is equally well received by both male and female learners. Pearson correlation and multiple regression analyses demonstrated that motivation to learn (β = .512, p < .001) and ease of use (β = .341, p = .014) jointly explained 62.3% of the variance in overall perception (R² = .623, F = 22.87, p < .001). Findings suggest that carefully designed GBL environments can meaningfully foster positive attitudes and motivational dispositions toward mathematics in the early grades. Implications for instructional design, teacher professional development, and curriculum integration in Indonesian primary education are discussed.